A real-time model-based approach for the reconstruction of fluid flows induced by microorganisms - Kondratieva, Polina; Georgii, Joachim; Westermann, Rüdiger; Petermeier, Hannes; Kowalczyk, Wojciech; Delgado, Antonio (Experiments in Fluids, 2008)
An experiment on living microorganisms is conducted to gain insight into their motion and fluid exchange characteristics. Biocompatible microscopic particle image velocimetry (PIV)-systems are used to capture images of seeded particles in the induced fluid flows. To enhance the abilities of these devices we present a model-based approach for the reconstruction of admissible flow fields from captured images. A priori knowledge of the physical model of the flow is used to iteratively refine a predicted flow field. A physics-based filter operation generates a velocity field that is consistent with the model of incompressible laminar flows described by the Navier-Stokes equations. Interactive steering of the reconstruction process is achieved by exploiting programmable graphics hardware as a co-processor for numerical computations. To validate our method, we estimate velocity vector fields from synthetic image pairs of flow scenarios for which ground truth velocity fields exist and real-world image sequences of the flow induced by sessile microorganisms. © 2008 Springer-Verlag.
UnivIS-Import:2015-04-14:Pub.2008.tech.ITC.stmmec.arealt